(untitled) (Kew, 1992)
The standard reference for all botanists, herbarium managers and technicians involved with the making and maintenance of herbarium collections. Many figures and text illustrations. A translation of the English 3rd edition, published in 1998.
Keywords: Herbaria,Botanical specimens; Collection and preservation